Nurses’ experiences with initiating non-invasive ventilation therapy in a general ward setting with an intermediate care unit: A qualitative study - Grue, Mona; Hofsø, Kristin; Dihle, Alfhild; Steindal, Simen A. (Nordisk Tidsskrift for Helseforskning, 2023)
Treatment with non-invasive ventilation (NIV) can be conducted at general wards with an intermediate care room and can therefor potentially mitigate the pressure on the intensive care capacity. The aim of this study was to elucidate what nurses consider as important prerequisites for successfully initiating NIV treatment in general wards with an intermediate care room. The study employed a qualitative method with an exploratory and descriptive design. Individual semi-structured interviews were conducted with seven nurses. Data were analysed using systematic text condensation. The nurses considered that creating a safe relationship based on the patient’s needs through presence and attention, and having sufficient NIV competence, were prerequisites for successful initiation of NIV treatment. Furthermore, the successful initiation of NIV treatment requires nurses that can conduct diverse clinical and ethical assessments in order to assess the patient’s needs and the effectiveness of the NIV treatment. The novelty of this study is that it describes the initiation of NIV treatment in general wards with an intermediate care room.